Mass versus exclusive goods, and formal-sector employment - Reto Foellmi; Josef Zweimüller (University of Bern, Department of Economics, 2010)
We explore how the underemployment problem of less-developed economies is related to income inequality. Our crucial assumption is that consumers have non-homothetic preferences over differentiated products of formal-sector goods and thus that inequality affects the composition of aggregate demand via the price-setting behavior of formal-sector firms. We find that (i) high inequality divides the formal sector into mass producers (which charge low prices that are within the reach of the poor) and exclusive producers (which charge high prices and sell only to the rich); (ii) high inequality generates an equilibrium where many workers are crowded into the informal economy; and (iii) an increase in subsistence productivity raises the wages of unskilled workers and boosts employment due to the higher purchasing power of poorer households.
Keywords: E25; D30; D42; L16; E24; 330; income distribution; monopolistic competition; mark-ups; exclusion; Unterbeschäftigung; Einkommensverteilung; Monopolistischer Wettbewerb; Soziale Ungleichheit; Dualökonomie; Vierte Welt